Coronavirus and business - Harvard Business Review Press (Boston, Massachusetts : Harvard Business School Publishing Corporation, 2020)
"Coronavirus and business: the insights you need from Harvard Business Review is a compilation of sixteen recent articles from HBR.org. It provides you with essential thinking about keeping your company running remotely, managing your business through disaster and recovery, and finding it within yourself to lead with resilience through the crisis. Business is changing. Will you adapt or be left behind? Get up to speed and deepen your understanding of the topics that are shaping your company's future with the Insights You Need from Harvard Business Review series. Featuring HBR's smartest thinking on fast-moving issues--blockchain, cybersecurity, AI, and more--each book provides the foundational introduction and practical case studies your organization needs to compete today and collects the best research, interviews, and analysis to get it ready for tomorrow." -- provided by publisher.
Intro -- Contents -- Section 1: Managing Your Business -- Ch. 1: Lead Your Business Through the Coronavirus Crisis / by Martin Reeves, Nikolaus Lang, and Philipp Carlsson-Szlezak -- Ch. 2: 8 Questions Employers Should Ask About Coronavirus / by Jeff Levin-Scherz and Deana Allen -- Ch. 3: Prepare Your Supply Chain for Coronavirus / by James B. Rice, Jr. -- Ch. 4: What Are Companies' Legal Obligations Around Coronavirus? / by Peter Susser and Tahl Tyson -- Ch. 5: The Coronavirus Crisis Doesn't Have to Lead to Layoffs / by Atta Tarki, Paul Levy and Jeff Weiss -- Ch. 6: Delivery Technology Is Keeping Chinese Cities Afloat Through Coronavirus / Chengyi Lin -- Ch. 7: How Chinese Companies Have Responded to Coronavirus / by Martin Reeves, Lars Faeste, Cinthia Chen, Philipp Carlsson-Szlezak, and Kevin Whitaker -- Section 2: Managing Remote Teams -- Ch. 8: 15 Questions About Remote Work, Answered / Tsedal Neeley -- Ch. 9: A Guide to Managing Your (Newly) Remote Workers / by Barbara Z. Larson, Susan R. Vroman, and Erin E. Makarius -- Ch. 10: What It Takes to Run a Great Virtual Meeting / by Bob Frisch and Cary Greene ---- Ch. 11: How to Get People to Actually Participate in Virtual Meetings / by Justin Hale and Joseph Grenny -- Section 3: Leading Through the Crisis -- Ch. 12: Communicating Through the Coronavirus Crisis / Paul A. Argenti -- Ch. 13: Slow Down to Make Better Decisions in a Crisis / by Art Markman -- Ch. 14: Build Your Resilience in the Face of a Crisis / by Rasmus Hougaard, Jacqueline Carter, and Moses Mohan -- Ch. 15: Don't Hide Bad News in Times of Crisis / Amy C. Edmondson -- Ch. 16: How Bad Times Bring Out the Best in People / Bill Taylor -- About the contributors.
Description based upon online resource; title from PDF title page (viewed June 15, 2020).
Master record variable field(s) change: 650
Keywords: Industrial management; Coronaviruses -- Economic aspects; Industries -- Social aspects; Coronaviruses -- Economic aspects; Industrial management; Industries -- Social aspects; elektronické knihy; electronic books